Penerapan Metode Simple Additive Weighting untuk Pemilihan Kios Kosong di Pasar Tradisional Berbasis Tag-Lokasi - Syafira Salsabila; Diana Laily Fithri; Supriyono Supriyono (IDEALIS : InDonEsiA journaL Information System, 2026)
As a public facility, traditional markets play an important role in supporting the economic activities of the community, particularly for micro and small business actors. However, kiosk management in traditional markets is still carried out manually, making it prone to delayed data updates and data loss. This research is directed toward designing and implementing a tag-location-based kiosk monitoring information system integrated with the Simple Additive Weighting (SAW) method to support the prioritization of vacant kiosks at Mayong Market and Kalinyamatan Market, Jepara Regency. The novelty of this research lies in the application of a tag-location feature integrated with the Simple Additive Weighting (SAW) method to support kiosk monitoring and vacant kiosk prioritization within a single system. The system was developed using the Waterfall method by utilizing latitude and longitude coordinates integrated with a digital map to support visual and real-time monitoring of kiosk location and occupancy status. The SAW method was applied to 163 vacant kiosks, consisting of 69 kiosks at Mayong Market and 94 kiosks at Kalinyamatan Market. The results show that at Mayong Market, kiosk LT2.IV/10 obtained the highest SAW score of 0.96, while at Kalinyamatan Market, kiosk PKL.U/15 obtained the highest score of 1.00. Black Box Testing on 10 test scenarios showed that all system functions ran according to user requirements. The integration of the tag-location feature with the Simple Additive Weighting (SAW) method can serve as an approach in developing a location-based decision support system for the management of traditional market kiosks.